2010
DOI: 10.1186/1471-2458-10-386
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tooth loss and mortality in 80-year-old Japanese community-dwelling subjects

Abstract: BackgroundFindings from several studies suggest associations between tooth loss and health outcomes, including malnutrition, poor quality of life, and mortality, in older individuals. However, limited information is available regarding whether those associations remain true in very elderly subjects after adequately considering confounding factors such as sex and smoking status. Herein, we determined whether the number of teeth in 80-year-old subjects is an independent predictor of mortality.MethodsWe initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
3
44
0
5
Order By: Relevance
“…Other studies have indicated that economic and environmental factors generally affect the health behaviors of the elderly [48,49]. In terms of the mean score of the elderly in the sample areas, significant differences were observed among most of the eleven items on health behaviors.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies have indicated that economic and environmental factors generally affect the health behaviors of the elderly [48,49]. In terms of the mean score of the elderly in the sample areas, significant differences were observed among most of the eleven items on health behaviors.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, factors concerning oral status, inflammation, and function have been investigated for the same purpose [2931]. Recently, one study investigated the association between MOF and mortality in older Japanese adults, and reported that MOF was independently associated with all-cause mortality in males [14].…”
Section: Discussionmentioning
confidence: 99%
“…[68] Periodontal inflammation could increase mortality associated with cardiovascular or chronic heart disease. Tooth loss and periodontal inflammation were associated with various systemic diseases, including stroke, dementia, pneumonia, osteoporosis, cardiovascular disease, diabetes mellitus, rheumatoid arthritis, and erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%